SOLUTION MODELS FOR THE SERBIAN NATIONAL QUESTION IN MONTENEGRO - Stanković, Vladan (Political Review, 2023)
In this scientific paper, the author offered several institutional models for solving the open questions of the position of Serbs in unitary Montenegro. In the paper, the author singled out the following political and legal models of regulating national relations in Montenegro: consociativeness, constitutivity and cross-border cooperation. None of these models violates the territorial integrity of Montenegro, and enables the realization of individual and collective rights of Serbs in Montenegro, protecting their survival.
Keywords: Serbian national question; identity; Serbs; Montenegrins; Montenegrin nationalism; Montenegrinism